A Study into the Tourism Development Process - The Singapore River Revitalization Project - Chan, Heng Lum (2008)
In 2005, in order to arrest further decline in tourist arrivals, the Singapore government moved aggressively to woo new tourism development projects so as to regain its competitiveness and attractiveness as a tourist destination. Responding to the challenge to meet tourism targets set by the government, the Singapore Tourism Board identified the Singapore River as a district to be revitalized to meet the needs of new tourism segments. It is more than two years since the project on the revitalization of the Singapore River was initiated, and yet there has been no new development in the district. This dissertation investigates why the revitalization of the Singapore River project has not taken off given that a Master Plan has been drawn. The research focuses on the conditions or combination of conditions that contributed to the project in its present state, and whether the tourism development planning process affected its outcome.